2016
DOI: 10.1590/0103-8478cr20141500
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic potential of dillapiole-rich essential oil with synthetic pyrethroid insecticides against fall armyworm

Abstract: The objective of this study was to evaluate the synergy and response homogeneity of the Spodoptera frugiperda larvae population to the Piper aduncum essential oil in combination with pyrethroid insecticides (alpha-cypermethrin, betacypermethrin, fenpropathrin, and gamma-cyhalothrin) 5) e Fenpropatrina (FS=34,77), quando combinados com o óleo essencial de P. aduncum. Já por contato tópico, ocorreu significativa potencialização somente dos inseticidas alfa-Cipermetrina (FS=7,68), Fenpropatrina (FS=3,48)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…Among the compounds that are synthesized by the secondary metabolism of plants, terpenoids are a rich source of bioactive molecules that exhibit toxicity to various pests (Ali et al, 2010;Lima et al, 2013;Lima et al, 2009;Silva et al, 2010). Some studies have shown that these compounds act as inhibitors of AChE, impair oviposition (Alexenizer;Dorn, 2007;Cavalcante;Vasconcelos, 2006) and cellular respiration (Yu, 2008) and act as synergists of other bioactive agents (Fazolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the compounds that are synthesized by the secondary metabolism of plants, terpenoids are a rich source of bioactive molecules that exhibit toxicity to various pests (Ali et al, 2010;Lima et al, 2013;Lima et al, 2009;Silva et al, 2010). Some studies have shown that these compounds act as inhibitors of AChE, impair oviposition (Alexenizer;Dorn, 2007;Cavalcante;Vasconcelos, 2006) and cellular respiration (Yu, 2008) and act as synergists of other bioactive agents (Fazolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, insecticides used in combination can enhance their toxicity compared to their individual use (Khann et al, 2013). A good example of this combination is a mixture of pyrethroid, safrole and rotenone (terpenoids), known to inhibit the cytochrome P450, which is the main route of metabolism for pesticides (Fazolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Esta, talvez, seja a razão de os inseticidas do grupo dos piretroides avaliados neste experimento serem sinergizados com OEPA, indistintamente nas duas vias de contaminação e doses subletais ou concentrações equivalentes às respectivas DL 50 e CL 50 do óleo essencial, uma vez que a presença do grupo metilenodioxifenil em sua composição justifica o efeito sinérgico para esse grupo de inseticidas (Mukerjee & SAXENA, 1979;Bernard et al, 1990: Fazolin et al, 2016.…”
Section: Combinações De Inseticidasunclassified
“…Potencial sinérgico do óleo de Piper aduncum para inseticidas formulados com misturas de princípios ativos de compostos aromáticos essencialmente fenilpropanoidicos dos tipos lignanas e neolignanas, além da ocorrência de terpenos, flavonoides e outras classes de produtos naturais (Gottlieb et al, 1995) O óleo rico em dilapiol, obtido de plantas de Piper aduncum L. (Piperaceae), é uma opção à produção de lignanas sinérgicas, comprovando esse efeito para inseticidas do grupo dos piretroides (Mukerjee & Saxena, 1979;Bernard et al, 1990;Fazolin et al, 2016), uma vez que esse composto secundário atua no processo detoxificativo dos insetos por possuir uma associação de lignanas ao grupo metilenodioxifenil, tratando-se de uma característica das piperáceas, considerada importante inibidora de monoxigenases do citocromo P450 (Bernard et al, 1990). Essa espécie de piperácea, com altos teores de dilapiol (Maia et al, 1998), é abundante na Amazônia Ocidental e apresenta viabilidade de produção em escala comercial.…”
unclassified
“…It is known that combinations between different products can promote greater toxicity to insects, since a compound can potentiate the action of another active ingredient by weakening the insect detoxification system, acting on the inhibition of P450 enzymes and esterases (Khan et al, 2013;Fazolin et al, 2016). This method may allow the reduction of insecticide doses, while maintaining toxicity to pests.…”
Section: Introductionmentioning
confidence: 99%